Strong deviations from the NO-NO2-O-3 photostationary state in the Pearl River Delta: Indications of active peroxy radical and chlorine radical chemistry - Ma, Y. F.; Lu, K. D.; Chou, C. C. K.; Li, X. Q.; Zhang, Y. H. (Atmospheric EnvironmentAtmospheric Environment, 2017)
Simultaneous measurements of meteorological data, trace gases, and volatile organic compounds were made in two regional sites, viz. Backgarden and Kaiping, in the Pearl River Delta (PRD) during summer and autumn, respectively. The strong deviations from the NO-NO2-O-3 Photostationary State, quantified by the leighton ratios, are carefully deduced through a comprehensive data set consist of the high-quality measurements of NO, NO2, O-3 and JNoz as well as the peroxy radical measurements. This is the first report of the Leighton ratio in China, with relatively high recorded values of 2.3 +/- 0.4 (Backgarden) and 3.1 +/- 1.4 (Kaiping), suggesting a strongly oxidising atmosphere in the PRD, typical of the ozone pollution season. A sensitivity analysis using a zero-dimensional chemical box model based on the regional atmospheric chemistry mechanism, version 2 (RACM2) constrained by the experimental measurements, indicated that peroxy radicals account for 70 (Backgarden) and 66% (Kaiping) of the observed positive deviations from the NOx photostationary state (characterized by a Leighton ratio of 1) on average. We consider that the remaining deviations result from neglecting the effects of chlorine chemistry, so We introduced a Cl chemistry module into RACM2, and the modelled results for Cl were as follows: 4.7 x 10(-4) pptv in Backgarden and 1.3 x 10(-3) pptv in Kaiping; these results are lower than the CI concentration derived from the NOx photostationary state. More work is required to confirm the role of additional peroxy radical sources at both high and low NOx regimes, as well as that of the halogen radicals, in perturbing the NO-NOx-O-3 cycle, which would significantly enhance trace gas removal and photochemical ozone production. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: airborne observations; atmospheric chemistry; boundary-layer; chlorine chemistry; leighton ratio; ozone production; pearl river delta; peroxy radical; racm2; reactive chlorine; regional air-quality; relative-humidity; tropospheric chemistry; united-states; urban atmosphere